Simulating flood disaster using augmented reality application / Nur Syazana Yahaya and Nurul Hidayah Mat Zain - Yahaya, Nur Syazana; Mat Zain, Nurul Hidayah (College of Computing, Informatics, and Mathematics, 2024)
This study introduces the Flood Survival Augmented Reality (AR) application as a solution for young adults unfamiliar with floods and seeking to learn more about flood preparedness. The application was developed using Agile Methodology and addressed the issues of lack of awareness of flood risks and the lack of preparation necessary to face frequent flood disasters. By creating an immersive AR application, it helps individuals gain a better understanding of how to prepare for flood disaster scenarios, emphasizes the importance of flood preparation, and aids in learning the ideal course of action when flood disasters occur. The objectives of this project are to create 3D models of objects for simulating flood disasters, to develop a flood disaster simulation application, and to evaluate the usability of the flood disaster simulation application. Recent evaluations confirmed its usability score to be 73.5% on the System Usability Scale (SUS), indicating good usability of the application.